The ATLAS EventIndex: architecture, design choices, deployment and first operation experience. Issue 4 (December 2015) - Barberis, D.; Zárate, S.E. Cárdenas; Cranshaw, J.; Favareto, A.; Casaní, Á. Fernández; Gallas, E.J.; Glasman, C.; González de la Hoz, S.; Hřivnáč, J.; Malon, D.; Prokoshin, F.; Cairols, J. Salt; et al.
Abstract: The EventIndex is the complete catalogue of all ATLAS events, keeping the references to all files that contain a given event in any processing stage. It replaces the TAG database, which had been in use during LHC Run 1. For each event it contains its identifiers, the trigger pattern and the GUIDs of the files containing it. Major use cases are event picking, feeding the Event Service used on some production sites, and technical checks of the completion and consistency of processing campaigns. The system design is highly modular so that its components (data collection system, storage system based on Hadoop, query web service and interfaces to other ATLAS systems) could be developed separately and in parallel during LSI. The EventIndex is in operation for the start of LHC Run 2. This paper describes the high-level system architecture, the technical design choices and the deployment process and issues. The performance of the data collection and storage systems, as well as the query services, are also reported.